Behavior of Expansive Clay of Ngawi Region (East Java) Under Water Content Variation - Agus Tugas Sudjianto; Kabul Basah Suryolelono; Ahmad Rifa’i; Indrasurya B Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2009)
When expansive clay is wetted, deformations occur both vertically and laterally. If it is tested in an oedometer ring apparatus the lateral deformation will be restrained by the wall of the ring. This paper present the results of an experimental investigation using modified oedometer test for measuring the vertical and lateral swelling potential and lateral pressure of disturbed expansive clay soil. Series of modified oedometer tests were conducted with initial water content of 20%, 25% and 30%, to predict the vertical and lateral swelling potential and lateral swell pressure. The results of the test show that the percentages of the vertical swell is bigger than the lateral swell. Both vertical and lateral swell, linearly decrease with increasing initial water content. The lateral swell pressure also decreases with increasing initial water content.